Antagonism by taxol of effects of microtubule-disrupting agents on lymphocyte cAMP metabolism and cell function. - Wolberg, G (1984)
Several microtubule-disrupting agents (colchicine, demecolcine, vinblastine, vincristine, podophyllotoxin, and nocodazole) have been shown to inhibit lymphocyte-mediated cytolysis. These agents also enhanced the prostaglandin E1-induced rise in cAMP levels in these cytolytic lymphocytes. Taxol, a natural product alkaloid that has been shown to enhance microtubule polymerization and to stabilize microtubules, antagonized both of these effects of the microtubule-disrupting agents in the cytolytic lymphocytes. Taxol also antagonized the enhancement of cAMP increases by colchicine in lymphocytes stimulated by 2-chloroadenosine, isoproterenol, and cholera toxin. The enhancement of the prostaglandin E1-induced cAMP response caused by treatment of the lymphocytes with either cytochalasin B or 3-deazaadenosine in the presence or absence of L-homocysteine was not antagonized by taxol. Taxol, colchicine, or the combination of these two agents did not affect ATP levels in cytolytic lymphocytes. These results support a modulatory role for microtubules in both the cytolytic process and the production of cAMP in these lymphocytes.